Reading Habits of Juveniles in the Observation Homes of Tamil Nadu, India - Christal Dora, D.; Balasubramanian, P. (Indian Journal of Information Sources and Services, 2021)
We all understand that the children are the life deposits of the society, supports of the nation building processes and clearly stated energy stored basins of any realm and the builders of the upcoming world. They are the superlative resources of any country and hence every effort should be made to provide them equal opportunities for their development. Some children who are in conflict with laws by committing crimes are keeping on increasing in the recent times. The reason behind this situation are poverty prevailing in the families, poor educational status of the parents and nature of dwelling places. But beyond all these features, the government machineries are trying to do something for the children who already have committed crimes whether petty or major and keep them in the observation homes to correct them on the one hand and to impart certain value based education and vocational activities on the other hand. Reading is a powerful tool for people in every walk of life, but it takes on special significance for inmates. Reading books not only builds their knowledge and vocabulary, but it also develops their capacity for internal reflection - a crucial skill often lacking among delinquents. The present study is an attempt to analyse reading habits of Juveniles in the observation homes of Tamil Nadu.